Ready access to 7,8-dihydroindolo[2,3-d][1]benzazepine-6(5H)-one scaffold and analogues via early-stage Fischer ring-closure reaction - Kuznetcova, Irina; Bacher, Felix; Vegh, Daniel; Chuang, Hsiang-Yu; Arion, Vladimir B. (Beilstein Journal of Organic Chemistry, 2022)
Paullone isomers are known as inhibitors of tubulin polymerase and cyclin dependent kinases (Cdks), which are potential targets for cancer chemotherapy. Herein we report an efficient and clean pathway to the fourth isomer, which remained elusive so far, namely 7,8-dihydroindolo[2,3-d][1]benzazepin-6(5H)-one. Moreover, we demonstrate the generality of our pathway by synthesizing two closely related analogues, one containing a bromo substituent and the other one incorporating an 8-membered instead of a 7-membered ring. The key transformation in this four-step synthesis, with an overall yield of 29%, is the Fischer indole reaction of 2-nitrophenylacetyl acetoacetate with 1-benzyl-1-phenylhydrazine in acetic acid that delivers methyl 2-(1-benzyl-3-(2-nitrophenyl)-1H-indol-2-yl)acetate in 55% yield.
Keywords: anticancer; Fischer indole synthesis; Heck reaction; heterocyclic compounds; indolobenzazepines; latonduines; paullones

(untitled) - Kadagathur, M.; Patra, S.; Sigalapalli, D. K.; Shankaraiah, N.; Tangellamudi, N. D. (Org. Biomol. Chem., 2021)

(untitled) - Kunick, C. (Arch. Pharm. (Weinheim, Ger.), 1992)

(untitled) - Singh, A. K.; Raj, V.; Saha, S. (Eur. J. Med. Chem., 2017)

(untitled) - Joucla, L.; Popowycz, F.; Lozach, O.; Meijer, L.; Joseph, B. (Helv. Chim. Acta, 2007)

(untitled) - Putey, A.; Popowycz, F.; Do, Q.-T.; Bernard, P.; Talapatra, S. K.; Kozielski, F.; Galmarini, C. M.; Joseph, B. (J. Med. Chem., 2009)

(untitled) - Putey, A.; Joucla, L.; Picot, L.; Besson, T.; Joseph, B. (Tetrahedron, 2007)

Medicinal Organometallic Chemistry - Mulcahy, S. P.; Meggers, E. (Organometallics as Structural Scaffolds for Enzyme Inhibitor Design, 2010)

Advances in Organometallic Chemistry and Catalysis - Primik, M. F.; Filak, L. K.; Arion, V. B. (Metal-Based Indolobenzazepines and Indoloquinolines: From Moderate CDK Inhibitors to Potential Antitumor Drugs, 2013)

(untitled) - Filak, L. K.; Kalinowski, D. S.; Bauer, T. J.; Richardson, D. R.; Arion, V. B. (Inorg. Chem., 2014)

(untitled) - Dobrov, A.; Göschl, S.; Jakupec, M. A.; Popović-Bijelić, A.; Gräslund, A.; Rapta, P.; Arion, V. B. (Chem. Commun., 2013)

(untitled) - Primik, M. F.; Göschl, S.; Meier, S. M.; Eberherr, N.; Jakupec, M. A.; Enyedy, É. A.; Novitchi, G.; Arion, V. B. (Inorg. Chem., 2013)

(untitled) - Filak, L. K.; Göschl, S.; Heffeter, P.; Ghannadzadeh Samper, K.; Egger, A. E.; Jakupec, M. A.; Keppler, B. K.; Berger, W.; Arion, V. B. (Organometallics, 2013)

(untitled) - Arion, V. B.; Dobrov, A.; Göschl, S.; Jakupec, M. A.; Keppler, B. K.; Rapta, P. (Chem. Commun., 2012)

(untitled) - Filak, L. K.; Göschl, S.; Hackl, S.; Jakupec, M. A.; Arion, V. B. (Inorg. Chim. Acta, 2012)

(untitled) - Mühlgassner, G.; Bartel, C.; Schmid, W. F.; Jakupec, M. A.; Arion, V. B.; Keppler, B. K. (J. Inorg. Biochem., 2012)

(untitled) - Primik, M. F.; Göschl, S.; Jakupec, M. A.; Roller, A.; Keppler, B. K.; Arion, V. B. (Inorg. Chem., 2010)

(untitled) - Filak, L. K.; Mühlgassner, G.; Jakupec, M. A.; Heffeter, P.; Berger, W.; Arion, V. B.; Keppler, B. K. (J. Biol. Inorg. Chem., 2010)

(untitled) - Primik, M. F.; Mühlgassner, G.; Jakupec, M. A.; Zava, O.; Dyson, P. J.; Arion, V. B.; Keppler, B. K. (Inorg. Chem., 2010)

(untitled) - Schmid, W. F.; John, R. O.; Arion, V. B.; Jakupec, M. A.; Keppler, B. K. (Organometallics, 2007)

(untitled) - Schmid, W. F.; John, R. O.; Mühlgassner, G.; Heffeter, P.; Jakupec, M. A.; Galanski, M.; Berger, W.; Arion, V. B.; Keppler, B. K. (J. Med. Chem., 2007)

(untitled) - Schmid, W. F.; Zorbas-Seifried, S.; John, R. O.; Arion, V. B.; Jakupec, M. A.; Roller, A.; Galanski, M.; Chiorescu, I.; Zorbas, H.; Keppler, B. K. (Inorg. Chem., 2007)

(untitled) - Bacher, F.; Wittmann, C.; Nové, M.; Spengler, G.; Marć, M. A.; Enyedy, E. A.; Darvasiová, D.; Rapta, P.; Reiner, T.; Arion, V. B. (Dalton Trans., 2019)

(untitled) - Bremner, J. B.; Sengpracha, W. (Tetrahedron, 2005)

(untitled) - Joucla, L.; Putey, A.; Joseph, B. (Tetrahedron Lett., 2005)

(untitled) - Agarwal, P. K.; Sawant, D.; Sharma, S.; Kundu, B. (Eur. J. Org. Chem., 2009)

(untitled) - Firmansjah, L.; Fu, G. C. (J. Am. Chem. Soc., 2007)

(untitled) - Mendoza-Figueroa, H. L.; Serrano-Alva, M. T.; Aparicio-Ozores, G.; Martínez-Gudiño, G.; Suárez-Castillo, O. R.; Pérez-Rojas, N. A.; Morales-Ríos, M. S. (Med. Chem. Res., 2018)

(untitled) - Adams, R.; Thal, A. F. (Org. Synth., 1922)

(untitled) - Sharpe, R. J.; Johnson, J. S. (J. Org. Chem., 2015)

(untitled) - Lepri, S.; Ceccarelli, M.; Milani, N.; Tortorella, S.; Cucco, A.; Valeri, A.; Goracci, L.; Brink, A.; Cruciani, G. (Proc. Natl. Acad. Sci. U. S. A., 2017)

(untitled) - Podlech, J. (J. Prakt. Chem./Chem.-Ztg., 1998)

(untitled) - Parker, A. N.; Martin, M. C.; Shenje, R.; France, S. (Org. Lett., 2019)

(untitled) - Matell, M. (Ark. Kemi, 1956)

(untitled) - Aoyama, T.; Shioiri, T. (Chem. Pharm. Bull., 1981)

(untitled) - Jiao, L.; Bach, T. (J. Am. Chem. Soc., 2011)

(untitled) - Peng, L.; Zhang, T.; Li, Y.; Li, Y. (Synth. Commun., 2002)

(untitled) - Liu, C.; Zhu, X.; Zhang, P.; Yang, H.; Zhu, C.; Fu, H. (iScience, 2018)

(untitled) - Teotino, U. M. (Gazz. Chim. Ital., 1959)

(untitled) - Drissi-Amraoui, S. (Synlett, 2015)

(untitled) - Zhou, Z.-L.; Keana, J. F. W. (J. Org. Chem., 1999)

(untitled) - Srinivasa Rao, T.; Pandey, P. S. (Synth. Commun., 2004)

(untitled) - Haddach, A. A.; Kelleman, A.; Deaton-Rewolinski, M. V. (Tetrahedron Lett., 2002)

(untitled) - Watanabe, T.; Kobayashi, A.; Nishiura, M.; Takahashi, H.; Usui, T.; Kamiyama, I.; Mochizuki, N.; Noritake, K.; Yokoyama, Y.; Murakami, Y. (Chem. Pharm. Bull., 1991)

(untitled) - Bunce, R. A.; Nammalwar, B. (J. Heterocycl. Chem., 2009)

(untitled) - Jana, G. K.; Sinha, S. (Tetrahedron, 2012)

(untitled) - Banwell, M. G.; Lupton, D. W.; Ma, X.; Renner, J.; Sydnes, M. O. (Org. Lett., 2004)

(untitled) - Roskoski, R., Jr (Pharmacol. Res., 2015)